Palliative endovascular treatment of cancer-related iliocaval obstructive disease: technical and clinical outcomes. (April 2016) - Maleux, Geert; Vertenten, Bart; Laenen, Annouschka; De Wever, Liesbeth; Heye, Sam; Clement, Paul; Oyen, Raymond
Background: Cancer-related obstruction of large abdominal and pelvic veins might become symptomatic with clinical signs of lower limb venous congestion. Technical and clinical outcome after interventional treatment is not well studied yet. Purpose: To retrospectively assess the technical and clinical outcome of endovascular management of symptomatic cancer-related iliocaval venous obstructive disease. Material and Methods: From 1998 to 2013, 19 patients (15 men, 4 women; mean age, 63.6 years) referred for interventional treatment of cancer-related iliocaval obstructive disease were identified. Patients' symptoms included unilateral ( n  = 16; 84%) or bilateral ( n  = 3; 16%) painful swelling of the lower limbs. Patients' demographics as well as interventional and clinical outcome data were collected. Results: All 19 patients underwent, under local anesthesia, stenting of the iliac vein ( n  = 16; 84%) or inferior vena cava ( n  = 3; 16%). Immediate technical success ( n  = 19) was 100%; immediate clinical success ( n  = 18) was 94.7%. During follow-up, seven patients (36.8%) presented with recurrent symptoms of painful limb swelling. Estimated survival after 3 and 6 months was 68.4% (95% confidence interval [CI], 47.8–82.3%) and 19.8% (95% CI, 11.9–29.2%), respectively. Conclusion: Endovascular stenting of cancer-related iliocaval venous obstructive disease is safe and results in immediate relief of symptoms. However, recurrent venous obstruction is common. At 3 months follow-up, the majority of patients with iliac vein stenting were still alive.